Gonadal Failure Is Common in Long-Term Survivors of Childhood High-Risk Neuroblastoma Treated With High-Dose Chemotherapy and Autologous Stem Cell Rescue - Utriainen, Pauliina; Suominen, Anu; Mäkitie, Outi; Jahnukainen, Kirsi (Frontiers in Endocrinology, 2019)
Background: Neuroblastoma is the most common extra-cranial solid tumor in children. Intensive therapy including autologous stem-cell transplantation (HSCT) has improved the poor prognosis of high-risk neuroblastoma (HR-NBL) but may impair gonadal function. Objectives: To investigate the gonadal function and fertility in long-term survivors of childhood HR-NBL. Design: A cohort including all Finnish (n=20; 11 females) long-term (>10 yrs) survivors of HR-NBL and an age- and sex-matched control group (n=20) was examined at a median age of 22 (16-30) years. Oncologic treatments, pubertal timing, hormonal therapies and the number of off-spring were recorded, and pituitary and gonadal hormones were measured. Results: Altogether 16/20 of the long-term survivors of HR-NBL entered puberty spontaneously; puberty was hormonally induced in 4 survivors (3 females). Among the 8/11 female survivors with spontaneous puberty, 7 had spontaneous menarche, but 5/8 developed ovarian failure soon after puberty. Nine females currently needed estrogen substitution. AMH, a marker of ovarian reserve, was lower in the female survivors than controls (median 0.02 vs. 1.7 µg/l, p<0.001). As a group, male survivors had smaller testicular size (8.5 vs. 39 ml, p<0.001) and lower inhibin B (<10 vs. 170 ng/l, p<0.001) compared with control males, with altogether 6/9 survivor males fulfilling the criteria of gonadal failure (absent puberty, small testicle size or increased FSH with need of testosterone substitution). Gonadal failure was more common in female and male survivors treated with total-body irradiation. Three survivors (1 male) had offspring, all treated without total-body irradiation and moderate dose of alkylating chemotherapy. Growth velocity was compromised in all survivors after HR-NBL diagnosis, with absent pubertal growth spurt in 7/17 survivors with complete growth data. Conclusion: Gonadal failure is common in long-term survivors of HR-NBL treated with HSCT. Fertility may be preserved in some survivors treated without total-body irradiation.